A SYSTEMATIC LITERATURE REVIEW OF LEAN SIX SIGMA IN VARIOUS INDUSTRIES - Kurnia, Hibarkah; Purba, Humiras Hardi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2021)
The Lean Six Sigma / LSS approach has received a lot of attention in various industrial sectors, from the manufacturing industry to the service industry. More specific knowledge about Lean Six Sigma has grown rapidly. Much of the training and research on Lean Six Sigma is carried out in various industries. This literature review is related to LSS's purpose to provide an overview of Lean Six Sigma implementation in the manufacturing industry.Â The Lean Six Sigma approach introduced and implemented for a long time is DMAIC (Define, Measure, Analyze, Improve, and control). This paper discusses the published literature related to Six Sigma ranging from 2015 to 2020. This paper involves the study review of 50 papers related to the implementation of LSS of known database search, including Google Scholar, Elsevier, Science Direct, and other worldwide publishers. This literature review contains results from a variety of different perspectives. The perspective includes the focus of the industry, the focus of the number of distribution by country, the focus of the year of publication, and the number of publishers. This is useful for all types of manufacturing industries to find solutions to problems. The paper also provides advantages for researchers next to add to the literature.